2004
DOI: 10.1080/00016480310016893
|View full text |Cite
|
Sign up to set email alerts
|

Role of human papillomavirus in the development of head and neck squamous cell carcinomas

Abstract: Taken together, these data support the view that HPV-harbouring HNSCC can be considered a discrete tumour entity with, moreover, a favourable prognosis. Screening of patients, especially those with tonsillar cancers, for the presence of HPV may help to further optimize treatment protocols and to provide more accurate prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 15 publications
2
68
0
5
Order By: Relevance
“…The absence of p53 mutations in the tumor cell may allow an enhanced response to radiotherapy (Tachezy et al, 2005;Hoffmann et al, 2005). Hafkamp et al suggested that radiotherapy may decrease the ability of HPV-E6 and E7 to interact with p53 and pRb which supported the hypothesis above (Hafkamp et al, 2004). However, Ritchie et al found no statistically significant interaction between HPV status and radiotherapy on survival in oral and oropharyngeal cancers by considering separate effects for surgery and radiotherapy (Ritchie et al, 2003).…”
Section: Discussionmentioning
confidence: 60%
“…The absence of p53 mutations in the tumor cell may allow an enhanced response to radiotherapy (Tachezy et al, 2005;Hoffmann et al, 2005). Hafkamp et al suggested that radiotherapy may decrease the ability of HPV-E6 and E7 to interact with p53 and pRb which supported the hypothesis above (Hafkamp et al, 2004). However, Ritchie et al found no statistically significant interaction between HPV status and radiotherapy on survival in oral and oropharyngeal cancers by considering separate effects for surgery and radiotherapy (Ritchie et al, 2003).…”
Section: Discussionmentioning
confidence: 60%
“…The tonsil has squamous epithelium on the surface and reticulated epithelium in the crypts and may undergo metaplastic processes, producing an environment that may favour HPV infection and transformation, like in the cervical epithelium. It has been suggested that HPV-positive tonsillar carcinomas represent a separate tumour entity, which is less dependent on conventional HNSCC risk factors (29).…”
Section: Discussionmentioning
confidence: 99%
“…The deregulation of the p53 and pRb pathways in both HPV related andunrelated carcinogenic routes will ultimately result in a deregulation of the cell cycle and of the apoptotic process, finally leading to chromosome instability. 12,13 The occurrence of chromosome instability is considered to be a late event in HPV related carcinogenesis. In vitro studies with HPV-E6/E7 immortalized keratinocytes and raft cultures have shown that a persistent HPV infection is not sufficient for malignant transformation.…”
mentioning
confidence: 99%